Islamic norms for stock screening A comparison between the Kuala Lumpur Stock Exchange Islamic Index and the Dow Jones Islamic Market Index - Abdul Rahman, Azhar; Yahya, Mohd Azlan; Mohd Nasir, Mohd Herry (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to compare the criteria used among Islamic Indices, specifically between the Kuala Lumpur Stock Exchange Shari’ah Index (KLSESI) and the Dow Jones Islamic Market Index (DJIM) in screening a permissible company for investment purposes. The two controversial criteria examined are: level of debt and level of liquidity of company.Design/methodology/approach – The paper investigates the 642 companies listed on the Bursa Malaysia in 2006 as approved Shariah’s compliant companies by the Shari’ah Advisory Council of the KLSE. Findings – Overall, the results reveal that the KLSESI does not use both the criteria set by the DJIM as its measures during the screening process. As for the level of debt criterion, the results show that 44.07 percent of the companies listed under the KLSESI are highly geared. These companies depend heavily on debt to finance their capital. However, the results for the level of liquidity criterion are not as extreme as the level of debt where it shows only 17 percent of the companies listed under the KLSESI are highly liquid. The results also indicate that if both criteria are compared concurrently,only 198 out of 565 companies listed under the KLSESI conform to the criteria set up by the DJIM. Research limitations/implications – The main reasons why the differences exist among Islamic Indices are due to micro-factor as faced by Malaysian companies such as the limited amount of capital resources. The Shari’ah supervisory board of the respective indices represents the sole body that determines the rules or criteria to be used by each index. This explains why the indices differ from one country to another and efforts should be done by regulators in the respective countries to harmonize the differing criteria used.Originality/value – The paper represents the first study that compares the criteria used by two different indices regarding Islamic capital investment in a developing country.